Characterization of adverse events during the treatment with heberprot-p® in four cuban provinces - Alvarez Crespo, Alina Ramona; Alonso Carbonell, Liuba; Yara Alos, Isis Belkis; Garcia Milian, Ana Julia; Marrero Miragaya, María Acelia (Horizonte Sanitario, 2015)
Objective. The objective of this study and the reason that encouraged us to carry out this work was to characterize the adverse events reported during the treatment with Heberprot-P® in diffrent health institution/centers. Materials and Methods: Longitudinal, multicenter, postmarketing follow-up study of Heberprot-P®. Intensive surveillance was used as PS (pharmacosurveillance) method. The following variables were considered: presence or absence of AEs (adverse events); most frequently reported AEs; affcted organ system; serious AE according to cause conditioning both the event severity and type, and severity of ADRs (adverse drug reactions) and causality of AE reported as serious. Results: The presence of at least one AE was reported in 260 patients (59.1%). Burning sensation and pain in injection site, chills and shivering, were the four most frequently reported adverse events. A total of 11 events were identifid as serious. Conclusions : The intensive PS of the drug should be continued since all the routine medical practice data that could be contributed are essential for the purpose of enriching the drug’s safety profie